Role of Networking in enhancement of the progress of SMEs in Medchal District of Telangana Region - N. Lakshmi Gayathri, Prasad Babu Jayanthi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
With the launching of the cluster development programme in India by the UNIDO in 1997, promoting clusters as a strategy to enhance the competitiveness and to participate in the global value chain has been almost a celebrated strategy countrywide. The surge of various cluster schemes can be observed since 2000 onwards. Numerous Government and quails-government documents have acknowledged cluster development as the most important initiative to improve the performance of the MSMEs in the country.